PENDIDIKAN LIBERALISME DALAM TINJAUAN FILSAFAT PENDIDIKAN ISLAM - Suriyati; Hasmiati; Jamaluddin; Sudirman P (Faculty of Tarbiyah and Teacher Training, 2022)
This article aims to examine and describe how liberalism education is in a review of the philosophy of Islamic education. The type of research used is library research with the main source of books. This paper is compiled based on library research (library research). Literature review is a method by utilizing library sources as the main source in this research activity. The data collection method in this library research is to use documents obtained from books, journals, articles, papers, and the results of previous studies that are considered relevant by focusing on literature review. After the data is collected, content analysis is carried out in order to get the right and accurate conclusions. The focus in this research is liberalism and philosophy of Islamic education. The results of this study show that the depiction of Islamic values ​​to be achieved in an educational process based on Islamic teachings is gradual. Islam provides very clear information regarding the existence of human nature. The view of liberalism which has the essence of freedom, humans have a very significant role in developing their minds based on what they want.